Why care about integrated care? Part I. Demographics, finances and workforce: immovable objects facing mental health services. (January 2023) - Tracy, Derek K.; Holloway, Frank; Hanson, Kara; James, Adrian; Strathdee, Geraldine; Holmes, Dez; Kalidindi, Sridevi; Shergill, Sukhwinder S.
SUMMARY: Demands on health and social care are growing in quantity and complexity, with resources and staffing not projected to match this. The landmark NHS Long Term Plan calls for services in England to be delivered differently through integrated care systems (ICSs) that will better join commissioners and providers, and health and social care. The scale of these changes is immense, and the detail can feel confusing. However, they are important and will affect all clinicians in the public service. This three-part series provides a primer on integrated care, explaining why it is happening, how services are changing and why clinicians should get involved. In this first article we focus on the changing demographics, and the workforce and financial resources required to address these.